2020
DOI: 10.7150/jca.39626
|View full text |Cite
|
Sign up to set email alerts
|

Association of benign gynaecological diseases and risk of endometrial and ovarian cancers

Abstract: Objective: Gynaecologic benign diseases such uterine fibroids share similar pathogeneses with endometrial and ovarian cancers. Whether a history of uterine fibroids increases the risk of developing endometrial or ovarian cancers is controversial, due to uterine fibroids was self-reported in those studies. Methods: In our current case-control study, 268 women with endometrial cancer and 108 women with ovarian cancer were included. In addition, 500 women without gynaecological cancers were randomly selected as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…In our series, we confirmed that endometrial cancer appears in 3.6% of adenomyosis patients, followed by ovarian cancer (1.4%) and cervical cancer (0.8%) (Table 3). Well of note, the National Cancer Institute mentions that approximately 3.1 % of women will be diagnosed with uterine cancer, less than 2% with ovarian cancer and 0, 6% with cervical cancer at some point during their lifetime [31]. Thus, according to our data, we did not observe a significant risk of developing gynecological malignancy in women with adenomyosis compared to cases with no previous pathology of adenomyosis.…”
Section: Discussionsupporting
confidence: 55%
“…In our series, we confirmed that endometrial cancer appears in 3.6% of adenomyosis patients, followed by ovarian cancer (1.4%) and cervical cancer (0.8%) (Table 3). Well of note, the National Cancer Institute mentions that approximately 3.1 % of women will be diagnosed with uterine cancer, less than 2% with ovarian cancer and 0, 6% with cervical cancer at some point during their lifetime [31]. Thus, according to our data, we did not observe a significant risk of developing gynecological malignancy in women with adenomyosis compared to cases with no previous pathology of adenomyosis.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies have shown that endometriosis is associated with an increased risk of ovarian cancer, specifically endometrioid and clear cell ovarian subtypes [ 9 , 10 , 11 ]. However, contradictory evidence exists as to whether endometriosis and adenomyosis are associated with endometrial cancer [ 11 , 12 , 13 , 14 , 15 ]. Additionally, most studies included women with clinical or surgical endometriosis/adenomyosis, whereas histological diagnosis is still considered the gold standard [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, most studies included women with clinical or surgical endometriosis/adenomyosis, whereas histological diagnosis is still considered the gold standard [ 2 ]. Furthermore, studies on adenomyosis and endometrial cancer included small samples sizes [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is probable that the different results obtained in our study could be attributed to the sample size, as our study include a greater number of patients. In this line, Tseng et al [ 31 ] also identified, in a broader sample size, that patients with uterine fibroids had a 2.26-fold higher risk of developing ovarian cancer than patients without uterine fibroids, and this risk could significantly decrease after myomectomy or hysterectomy. However, further studies are required before drawing relevant conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational diabetes mellitus (GDM) constitutes one of the most representative and worrisome complications among pregnant women [ 31 ]. GDM is not only associated with adverse pregnancy outcomes but also has significant long-term implications on health conditions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%